2018
DOI: 10.3791/58687
|View full text |Cite
|
Sign up to set email alerts
|

RNA-based Reprogramming of Human Primary Fibroblasts into Induced Pluripotent Stem Cells

Abstract: Induced pluripotent stem cells (iPSCs) have proven to be a valuable tool to study human development and disease. Further advancing iPSCs as a regenerative therapeutic requires a safe, robust, and expedient reprogramming protocol. Here, we present a clinically relevant, step-by-step protocol for the extremely high-efficiency reprogramming of human dermal fibroblasts into iPSCs using a non-integrating approach. The core of the protocol consists of expressing pluripotency factors (SOX2, KLF4, cMYC, LIN28A, NANOG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Basic research in an orthotopic xenograft mouse model of glioblastoma showed that cell‐based therapy with miR‐302/367‐expressing cells inhibits tumor growth . Currently, researchers can generate high‐quality iPSCs from most fibroblast sources by transfection with reprogramming‐modified mRNAs and mature ESC‐specific miR‐367/302 mimics . Cancer stem cells also represent a new approach to understanding the origin of cancer.…”
Section: Microrna‐302 Cluster Is An Emerging Potential Biomarker or Tmentioning
confidence: 99%
“…Basic research in an orthotopic xenograft mouse model of glioblastoma showed that cell‐based therapy with miR‐302/367‐expressing cells inhibits tumor growth . Currently, researchers can generate high‐quality iPSCs from most fibroblast sources by transfection with reprogramming‐modified mRNAs and mature ESC‐specific miR‐367/302 mimics . Cancer stem cells also represent a new approach to understanding the origin of cancer.…”
Section: Microrna‐302 Cluster Is An Emerging Potential Biomarker or Tmentioning
confidence: 99%
“…In our studies, we obtained a reprogramming efficiency of 0.8% by applying the same protocol to NuFFs, this was probably caused by lab-to-lab or material variabilities. Furthermore, the use of adult fibroblasts or fibroblasts from diseased patients as well as the use of other somatic cells can result in other reprogramming efficiencies [6, 24, 37]. Therefore, reprogramming protocols should be tested and optimized for each cell type [7].…”
Section: Discussionmentioning
confidence: 99%
“…Human primary fibroblasts were reprogramed by introducing synthetic modified mRNAs coding for reprogramming proteins. MicroRNAs like miRNA-367/302s are used to reprogram human primary fibroblasts into iPSCs[ 39 ]. The mRNA transfection is foot print free reprogramming.…”
Section: Human Ipsc Reprogramming Methodsmentioning
confidence: 99%